Should Uniform Pricing Constraints be Imposed on Entrants? - Hoernig, Steffen (2019)
We analyse the effects of universal service obligations, such as uniform pricing, price caps and unbundling, on allocations in markets newly opened to competition, e.g. telecommunications. If uniform pricing is imposed not only on incumbents but also on entrants, entry may not result in competition if installed capacity is low, or may neglect high-cost areas if installed capacity or mandated coverage is high. These results hold no matter whether a price cap is in place or not, and do not depend on whether entry is capacity-based or facilitated through unbundling.